Transparent Liquid Multiple-Antenna Array with a High Gain and Beam Diversity for UHD TV Applications - Duy Tung Phan; Chang Won Jung (Journal of Electromagnetic Engineering and Science, 2022)
The design of television (TV) antennas for commercial use that operate on the ultra-high frequency (UHF) band has become more challenging given the relatively large size of these antennas and considering that they typically do not conform to aesthetically pleasing standards. This paper presents a transparent liquid multiple-antenna array for ultra-high-definition TV (UHD TV) applications (470–770 MHz; 48.5%). The motivation behind the use of multiple antennas is that a single transparent antenna normally performs poorly given the low conductivity of transparent conductors. The multiple-antenna array here consists of two saltwater antenna elements with high optical transparency (>90%). The antenna elements are organized in three working modes to achieve higher gain and omnidirectional characteristics. Experimental results find that the antenna in array mode shows a high gain of up to 5.27 dBi in the UHF band, while the diversity mode shows various beam patterns with good diversity gain outcomes. These results demonstrate the potential of the proposed multiple-antenna array to increase the reception rate of UHD TV applications.